Distal Radius Attachments of the Radiocarpal Ligaments: An Anatomical Study - Zumstein, M. A.; Hasan, A. P.; McGuire, D. T.; Eng, Kevin; Bain, Gregory Ian (Journal of Wrist Surgery, 2013)
Background Understanding the anatomy of the ligaments of the distal radius aids in the surgical repair of ligamentous injuries and the prediction of intraarticular fracture patterns.Purposes (1) to measure the horizontal and vertical distances of the origins of the radiocarpal ligaments from the most ulnar corner of the sigmoid notch and the joint line, respectively; and (2) to express them as a percentile of the total width of the bony distal radius.Methods We dissected 8 cadaveric specimens and identified the dorsal radiocarpal, radioscaphocapitate, and the long and short radiolunate ligaments.Results The dorsal radiocarpal ligament attached from the 16th to the 52nd percentile of the radial width. The radioscaphocapitate ligament attached around the radial styloid from the 86th percentile volarly to the 87th percentile dorsally. The long radiolunate ligament attached from the 59th to the 85th percentile, and the short radiolunate ligament attached from the 14th to the 41st percentile.Discussion There was a positive correlation between the radial width and the horizontal distance of the ligaments from the sigmoid notch. These findings may aid individualized surgical repair or reconstruction adjusted to patient size and enable further standardized research on distal radial fractures and their relationship with radiocarpal ligaments.
Keywords: distal radius; morphology; wrist ligaments